2014
DOI: 10.3390/antiox3010081
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Properties of Juniper Berry (Juniperus communis L.) Essential Oil. Action of the Essential Oil on the Antioxidant Protection of Saccharomyces cerevisiae Model Organism

Abstract: The essential oil of juniper berries (Juniperus communis L., Cupressaceae) is traditionally used for medicinal and flavoring purposes. As elucidated by gas chromatography/flame ionization detector (GC/FID) and gas chromatography/mass spectrometry (GC/MS methods), the juniper berry oil from Bulgaria is largely comprised of monoterpene hydrocarbons such as α-pinene (51.4%), myrcene (8.3%), sabinene (5.8%), limonene (5.1%) and β-pinene (5.0%). The antioxidant capacity of the essential oil was evaluated in vitro b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 41 publications
(64 reference statements)
3
103
1
Order By: Relevance
“…This is in accord with similar reports for juniper species from other regions (Elmastaş et al, 2006;Moein et al, 2010;Emami et al, 2011;Höferl et al, 2014;Cioanca et al, 2015;Elmhdwi et al, 2015). However, antioxidant activity as reported in this study did not correlate with the total content of phenolics and flavonoids, except for extracts obtained from cuttings of small seedlings, which shared the highest antioxidant activity with that of C2-type callus and in vitro shoots.…”
Section: Secondary Metabolites and Antioxidant Activitysupporting
confidence: 63%
“…This is in accord with similar reports for juniper species from other regions (Elmastaş et al, 2006;Moein et al, 2010;Emami et al, 2011;Höferl et al, 2014;Cioanca et al, 2015;Elmhdwi et al, 2015). However, antioxidant activity as reported in this study did not correlate with the total content of phenolics and flavonoids, except for extracts obtained from cuttings of small seedlings, which shared the highest antioxidant activity with that of C2-type callus and in vitro shoots.…”
Section: Secondary Metabolites and Antioxidant Activitysupporting
confidence: 63%
“…Previous studies have shown that juniper berries are rich in essential oils with 15-74 different components; the dominant being monoterpenes (α-pinene, myrcene, sabinene, limonene and β-pinene), followed by small amounts of sesquiterpenes and non-terpene components such as undecanone-2 and tricyclene (Okasaka et al 2006;Rezvani et al 2009;Sela et al 2011;Höferl et al 2014). As the non-viable seeds are totally devoid of storage reserves due to consumption by insect larvae (insect-attacked seeds) and developmental arrest of the storage organs and seed filling (empty and shriveled seeds), the spectral signature is presumably dominated by surface reflectance from the seed coats, which have terpenoids as chemical constituent.…”
Section: Discussionmentioning
confidence: 99%
“…58 Moreover, α-Pinene and Limonene rich essential oil prevented against lipid peroxidation in vitro and improved the ability of yeast cells to adapt to reactive oxygen species. 59 The scavenging effect of β-Pinene and Limonene and their ability to protect deoxyribose against degradation by free radicals have been demonstrated. 59 In the current study, the percentages of these compounds were higher in LEO from (L-SP).…”
Section: Reomentioning
confidence: 99%
“…59 The scavenging effect of β-Pinene and Limonene and their ability to protect deoxyribose against degradation by free radicals have been demonstrated. 59 In the current study, the percentages of these compounds were higher in LEO from (L-SP). For example, β-Pinene represented (4.65±0.48%) of LEO from (L-SP) and (3.83±0.24 %) of LEO from (L-JL).…”
Section: Reomentioning
confidence: 99%